Existence and multiple solutions to a discrete fourth order boundary value problem - Xia Liu (Advances in Difference Equations, 2018)
Abstract In this article, we study a discrete fourth order boundary value problem. By making use of variational methods and critical point theory, we obtain some criteria for the existence and multiple solutions. Moreover, two examples are included to illustrate the applicability of the main results.